2022
DOI: 10.3390/ijerph19148376
|View full text |Cite
|
Sign up to set email alerts
|

Employment Industry and Occupational Class in Relation to Serious Psychological Distress in the United States

Abstract: Occupational characteristics may influence serious psychological distress (SPD) and contribute to health inequities; yet, few studies have examined multiple employment industries and occupational classes in a large, racially diverse sample of the United States. Using data from the National Health Interview Survey, we investigated employment industry and occupational class in relation to SPD in the overall population and by race/ethnicity, gender, age, household income, and health status. We created eight emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Financial problems have a high association with psychological distress and mental well-being ( 63 , 64 ). Because role is often associated with social class, individuals who seem to carry more professional roles and have higher socio-economic status have better mental health than those who are in roles of direct labor ( 65 , 66 ). Even so, health care workers with higher levels of socio-economic status experience more serious psychological distress than the general public ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial problems have a high association with psychological distress and mental well-being ( 63 , 64 ). Because role is often associated with social class, individuals who seem to carry more professional roles and have higher socio-economic status have better mental health than those who are in roles of direct labor ( 65 , 66 ). Even so, health care workers with higher levels of socio-economic status experience more serious psychological distress than the general public ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also found that those people who met criteria for psychological distress were 5 times more likely to endorse suicidal thinking. The K6 instrument is a very brief tool that has been widely used with many populations ( 41 , 65 , 89 ). It is free and open access ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors use study designs and logics derived from epidemiology, community-based (participatory) research, and the social sciences, employing qualitative, quantitative, and mixed-methods approaches to gather their data and undertake their analyses. As we considered the research, we categorized it into three general but not mutually exclusive content groupings, as follows: Studies that highlight the ways in which work interacts with other social phenomena to influence health [ 1 , 2 , 3 , 4 , 5 ]; Studies that focus on the context in which work happens and emphasize the importance of that context in shaping work or health [ 6 , 7 , 8 , 9 ]; Studies that encourage us to think more expansively about work [ 10 , 11 ]. …”
mentioning
confidence: 99%
“…Studies that highlight the ways in which work interacts with other social phenomena to influence health [ 1 , 2 , 3 , 4 , 5 ];…”
mentioning
confidence: 99%